Disaggregated Approach of Regional Government Expenditure and Poverty Eradication in South Sulawesi, Indonesia - Andi Nur Ildha Arfanita; Fatmawati Fatmawati; Sultan Suhab (EcceS (Economics, Social, and Development Studies), 2023)
Government spending is one of the pillars of fiscal decentralisation which plays an important role in overcoming poverty. However, many empirical studies are still being debated, especially at the regional level. Government spending can contribute to reducing poverty depending on the type of government spending. This study focuses on specific types of government spending that contribute to productivity, such as government spending on infrastructure, health, education, and social assistance. The study aims to analyze the effect of regional government expenditures on infrastructure, education, health, social protection, and economic growth on poverty reduction. The measurements of poverty used in this study include Headcount Index, Poverty Gap Index, and Poverty Severity Index. The data were analyzed using a panel data regression from 2015-2020 through multiple regression models directly and indirectly. The estimation results of the direct effect show that only government spending on health can reduce poverty through its three indicators, while government spending on social protection is ineffective. Government expenditures on infrastructure and education are only significant in reducing the income gap between the poor and the depth of poverty. The indirect effect results in the four government spending types being statistically significant on all poverty indicators through accelerating economic growth. Therefore, economic growth at the regional level is an important variable that strengthens the relationship between government spending and poverty reduction for all poverty indicators in the region. In addition, government spending on social protection is helpful for the poor but needs to optimize its utilization with more precise targets.